Penyuluhan KB dan Sosialisasi Gerakan Konseling Kontrasepsi Menggunakan Aplikasi “KlikKB” Sebagai Upaya Penurunan Unmet Need KB di Kota Pekanbaru: Penyuluhan KB dan Sosialisasi Gerakan Konseling Kontrasepsi Menggunakan Aplikasi “KlikKB” Sebagai Upaya Penurunan Unmet Need KB di Kota Pekanbaru - Ismainar, Hetty; Marlina, Hastuti; Rahmalisa, Uci (STIKes Hang Tuah Pekanbaru, 2023)
In Indonesia the unmet need for family planning in 2017 reached 10.6%, Riau 25.6% (2021) while the national target (5%). The public's low level of knowledge or understanding about family planning and the reluctance of PUS to visit health services are the main problems. In order to simplify the family planning counseling process, in 2022 the government created the